Age Dependendent Efficacy of Ace Inhibitors Among Chinese Cardiovascular Patients During Hospitalization Phase - Hussain, Tabish; Shu, Li Yu; Adji, A Seid; Sosorburam, Tumenjavkhlan (Asian Journal of Medical Sciences, 2011)
Objective: Cardiac failure is a global burden among cardiovascular diseases, and major cause of morbidity and mortality especially among elderly age group. Angiotensin Converting Enzyme(ACE) inhibitors, remained the choice of treatment as they inhibit the renin angiotensin aldosterone system along with reduction in levels of pro-inflammatory cytokines, both of them are key factors in progression and complications of heart failure. The aim of this study was to rule out the effect of aging and efficacy of ACE inhibitor, Captopril, among Chinese cardiovascular patients with acute myocardial infarction (MI) during the hospitalization phase of therapy. Material & Methods: Randomized control trial at hospital of Tongji Medical College Wuhan, China over a period of more than 1 year from April 2009 till July 2010 recruiting patients in two stages. A total of 260 patients with mean age 65±8 years were recruited. All suffered from first time myocardial infarction and arrived in Cardiac emergency within 72 hours of the event. The participants were then randomly divided in study and control groups which were then further classified in sub-groups depending upon their age. Study group received ACE inhibitor Captopril in addition to standardized therapy while control group just received the conventional therapy for the event. Statistical analyses were done to formulate the corre-lation between multi-variables. Results: Participants were divided in Study group (N=150) (A and C, Young and Old) and the control group (N=110) (B and D, Young and Old). Survival rate was better among elderly on captopril in comparison to younger ones during the hospitalization. The Systolic blood pressure among study group was significantly lower than control group (132.9±16.3mmHg/84.7 ±9.1mmHg vs. 147.1±17.4mmHg/85.1 ±10.9mmHg, P<0.05).Patient’s survival was statistically significant with respect to age (P<0.001). Conclusion: Treatment with Captopril is definitely associated with improved short as well as long term cardiac prognosis and markedly. Captopril therapy is associated with improved long term prognosis and reduced cardiac mortality during the hospitalization phase of the therapy and recovery period. But the most significant finding is that the increased survival after taking Captopril was higher in elderly patients than in younger patients. ACE inhibitors like Captopril in proper dosage play a real vital beneficial role among elderly patients as compared to the younger ones, but still there is need to recruit a large cohort in different ethnic groups with different genetic makeup. Key Words: Myocardial infarction (MI); Ace-inhibitor; Aging DOI: 10.3126/ajms.v1i2.2947 Asian Journal of Medical Sciences 1 (2010) 59-63